Ethical conduct-do and general well-being among university students, moderated by religious internalization: An Islamic perspective - Daliman, Daliman (Universitas Muhammadiyah Surakarta, 2021)
Although topics related to well-being are being studied, those which focused on Islamic values, principles, and beliefs in this region is still sparse. The purpose of this study is to identify the correlation between (1) Islamic ethical conduct-do and the general Islamic well-being, (2) Islamic religious internalization and Islamic general well-being, and (3) Islamic ethical conduct-do and Islamic general well-being, moderated by Islamic religious internalization. Data collection was carried out in October 2019 and involved the 1st semester students of the 2019-2020 academic year in the Faculty of Psychology, Universitas Muhammadiyah Surakarta. The subjects were selected using parallel sampling by choosing students from parallel classes; as many as 74 students were selected. The research instruments met the requirements of convergent and discriminant validity, as well as reliability. Data analysis was undertaken with the help of the PLS moderation program. The results indicated the following: (1) Islamic ethical conduct-do has a positive significant relationship with university students’ Islamic general well-being; (2) Islamic religious internalization has a positive significant association with university students’ Islamic general well-being; and (3) Islamic ethical conduct-do was significantly correlated with university students’ Islamic general well-being, Islamic religious internalization as a moderator variable.Keywords: Islamic ethical conduct-do; Islamic general well-being; Islamic religious internalization; Islamic well-being; Islamic religiousness